Control de legalidad de detenciones en flagrancia por la fiscalía provincial corporativa especializada en delitos de violencia familiar, Maynas 2021 - Ocampo Mozombite, Letycia Nataly (2023)
This research work is focused, on the alleged violation of the right to personal liberty of citizens accused of committing a flagrant crime, with the objective of determining whether the Provincial Corporate Prosecutor's Office Specialized in Crimes of Violence Against the Woman and the Members of the Maynas Family Group, the adequate control of legality has been carried out on such arrests, produced in the period 2021. For which, an applied type of research and a descriptive correlational approach was developed; since, having identified the legal context where the problem arises, the variables are described, made up of the crime in flagrante and the control of legality, in order to measure the degree of relationship that exists between them, and to be able to arrive at a conclusion that allows affirming or rejecting the proposed hypothesis. Finally, the results obtained in the present investigation through the application of surveys and documentary analysis, allowed us to conclude that the adequate control of legality has not been carried out on police arrests in flagrant crime by the prosecutors of the aforementioned prosecutor's office during the period 2021, which must be carried out from the first moment that the police communication is committed in order to avoid the violation of the fundamental rights of the detainee through a duly motivated fiscal pronouncement.